2011
DOI: 10.4025/actascihealthsci.v33i1.8052
|View full text |Cite
|
Sign up to set email alerts
|

Vitamina C, carotenoides, fenólicos totais e atividade antioxidante de goiaba, manga e mamão procedentes da Ceasa do Estado de Minas Gerais

Abstract: RESUMO.Este estudo teve como objetivo analisar o conteúdo de compostos antioxidantes (ácido ascórbico -AA, ácido desidroascórbico -ADA, vitamina C total, licopeno, β-caroteno, β-criptoxantina e estimativa de compostos fenólicos) e avaliar a atividade antioxidante, em goiaba, manga e mamão. A análise de carotenoides e vitamina C foi realizada por Cromatografia Líquida de Alta Eficiência (CLAE). O teor de fenólicos totais foi determinado utilizando o reagente de Folin-Ciocalteu e leitura espectrofotométrica. A a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1
18

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 44 publications
0
21
1
18
Order By: Relevance
“…This difference is possibly due to either the thermal processing used to obtain the flour or a greater amount of lycopene being present in the pulp than in the guava peels. Oliveira et al (2011) also quantified the β-carotene in guava and reported values of 366.3 µg.100 g -1 , while Freire et al (2012) measured 490 µg.100 g -1 in guava, which is also higher than the value measured in this study.…”
Section: Resultscontrasting
confidence: 50%
See 2 more Smart Citations
“…This difference is possibly due to either the thermal processing used to obtain the flour or a greater amount of lycopene being present in the pulp than in the guava peels. Oliveira et al (2011) also quantified the β-carotene in guava and reported values of 366.3 µg.100 g -1 , while Freire et al (2012) measured 490 µg.100 g -1 in guava, which is also higher than the value measured in this study.…”
Section: Resultscontrasting
confidence: 50%
“…The differences in the levels of licopene and β-carotene may be partially explained by problems with bioavailability of lycopene from different food sources, as some types of fibers found in foods, such as pectin, can reduce the bioavailability of lycopene (Shi & Maguer, 2000). Oliveira et al (2011) reported much higher lycopene levels (6999.3 µg.100 g -1 ) in fresh and whole guava fruit compared to this study. This difference is possibly due to either the thermal processing used to obtain the flour or a greater amount of lycopene being present in the pulp than in the guava peels.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…The values obtained in the present studied are in accordance with those reported for other fruits such as jabuticaba (450 mg.100 g of pulp -1 ) (LIMA et al, 2008). Oliveira et al (2011) reported similar values of phenolic compounds in guava, but lower values were obtained in papaya and mango fruits from Brazil. Phenolic compounds and tannins have important antioxidant activity.…”
Section: Resultsmentioning
confidence: 75%
“…Oliveira et al (2011) found an average content of vitamin C of 0.80 mg g -1 for the fresh pulp of Formosa papaya. The amounts of vitamin C in the present study, based on fresh matter, found in the peel flour (0.44 and fiber since, according to ANVISA (Agência Nacional de Vigilância Sanitária, 2012), food with a content of 6% can be considered high in fiber.…”
Section: Resultsmentioning
confidence: 99%